2022
DOI: 10.3390/jfb13030104
|View full text |Cite
|
Sign up to set email alerts
|

Geometry-Based Computational Fluid Dynamic Model for Predicting the Biological Behavior of Bone Tissue Engineering Scaffolds

Abstract: The use of biocompatible and biodegradable porous scaffolds produced via additive manufacturing is one of the most common approaches in tissue engineering. The geometric design of tissue engineering scaffolds (e.g., pore size, pore shape, and pore distribution) has a significant impact on their biological behavior. Fluid flow dynamics are important for understanding blood flow through a porous structure, as they determine the transport of nutrients and oxygen to cells and the flushing of toxic waste. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The findings demonstrate that when β is 2/3, the proportion of high WSS (>0.03 Pa) is minimal, comprising only 0.45%. Previous experimental findings have indicated that cell proliferation and differentiation were favored when the WSS remains below 0.01 Pa at lower levels , and a WSS <0.03 Pa correlates with enhanced osteoblast differentiation . Considering the BISs’ favorable characteristics in terms of flow velocity distribution, permeability, and WSS, it emerges as an ideal choice for a porous orthopedic implant, but further biological experiments are still needed to verify it.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The findings demonstrate that when β is 2/3, the proportion of high WSS (>0.03 Pa) is minimal, comprising only 0.45%. Previous experimental findings have indicated that cell proliferation and differentiation were favored when the WSS remains below 0.01 Pa at lower levels , and a WSS <0.03 Pa correlates with enhanced osteoblast differentiation . Considering the BISs’ favorable characteristics in terms of flow velocity distribution, permeability, and WSS, it emerges as an ideal choice for a porous orthopedic implant, but further biological experiments are still needed to verify it.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Analysis of WSS distribution on each scaffold is quantified by measuring the surfaceaverage WSS, which is more accurate than the volume average followed in the previous work. 12 The total number of surfaces for each design of scaffold differs and ranges from 64 to 96. Surface-averaged WSS was calculated by multiplying the velocity gradient with the viscosity of the body fluid in each selected surface by installing a virtual probe.…”
Section: Effect Of Inlet Velocity On Pressure Dropmentioning
confidence: 99%
“…Biologically designed scaffolds have uniform pore sizes and complex architecture. 12 Machine learning (ML) algorithms have been applied to these CFD simulations to accelerate the design process, to reduce computational time and cost, and also to improve the accuracy of the results. The application of deep learning (DL) models, such as convolutional neural networks (CNNs) and recurrent neural networks (RNNs), to CFD simulations in tissue engineering has been increasingly utilized in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last few decades in tissue engineering have seen a disproportionate focus on the studies of control of cell fate through the control of properties of solid materials onto which the cells adhere, ranging from the chemical composition [ 4 ] to topography [ 5 ] to mechanical stiffness [ 6 ], leaving the hydrodynamic effects of the fluid medium on the cells understudied in comparison. It is known, however, that the dynamics of the fluid flow through three-dimensional scaffolds has a critical effect on the fate of cells seeded inside them [ 7 ] and that structures of the cellular junctions and cytoskeleton can be altered by controlling fluid flow regimens inside the cerebral microvasculature [ 8 ], likely affecting consciousness and cognition [ 9 ]. Therefore, it is clear that the investigation of the relationship between cell behavior and hydrodynamic properties of the medium in which they grow should be more copious than it is today.…”
Section: Introductionmentioning
confidence: 99%